2007
DOI: 10.1111/j.1540-8175.2007.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between QLAB and TomTec Full Volume Reconstruction for Real Time Three‐Dimensional Echocardiographic Quantification of Left Ventricular Volumes

Abstract: RT3DE with TomTec or QLAB software analysis provides accurate LV-EF assessment in cardiomyopathic patients with distorted LV geometry and adequate 2D image quality. However, LV volumes may be somewhat more underestimated with the current QLAB software version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 20 publications
(36 reference statements)
6
84
0
7
Order By: Relevance
“…Már szá-mos vizsgálat igazolta az RT3DE szerepét a BK-i térfogatok pontos mérésében kontrasztanyag használata mellett és a nélkül [31], függetlenül a vizsgálatok során alkalmazott szoftvertől [32,33]. Irodalmi adatok alapján az RT3DE az MRI-hez mérhető nagy pontosságot és reprodukálható-ságot mutat a BK-i térfogatok mérése során [32,33].…”
Section: A Bal Kamrai Méretek éS Térfogatok Méréseunclassified
See 2 more Smart Citations
“…Már szá-mos vizsgálat igazolta az RT3DE szerepét a BK-i térfogatok pontos mérésében kontrasztanyag használata mellett és a nélkül [31], függetlenül a vizsgálatok során alkalmazott szoftvertől [32,33]. Irodalmi adatok alapján az RT3DE az MRI-hez mérhető nagy pontosságot és reprodukálható-ságot mutat a BK-i térfogatok mérése során [32,33].…”
Section: A Bal Kamrai Méretek éS Térfogatok Méréseunclassified
“…Mivel a BK-i modell segítségével a globális és szegmentális BK-i végszisztolés és végdiasztolés térfogatértékek nagy pontossággal meghatározhatók, így globális és az egyes szegmentumokra vonatkoztatott EF is számítható [31,32,33]. Echokardiográfi ás kontrasztanyag alkalmazása mellett az RT3DE pontosabbnak bizonyult a BKfunkció meghatározásában, amelyet az MRI-hez mérhe-tő szorosabb korreláció és egyetértés, valamint az alacsonyabb intra-és interobserver variabilitás jellemzett [31].…”
Section: Ejekciós Frakció (Ef) Méréseunclassified
See 1 more Smart Citation
“…In addition, it is unclear whether the accuracy of 3D-transoesophageal echocardiography is similar in patients with a dilated or aneurysmal left ventricle. Several studies [21][22][23][24][25] have investigated the validation of 3D-transthoracic echocardiography in patients with cardiomyopathy. They show good agreement for measuring stroke volume.…”
mentioning
confidence: 99%
“…Relevant underestimation of 3D volumes has been reported in other automatic software tools, and parallel comparisons showed that the results obtained by different automatic tools did not differ significantly. 3,4,[18][19][20] However, automatic tools for quantitative analysis of 3D data sets are highly desirable because manual analysis of 3D data is extremely timeconsuming and impractical.…”
mentioning
confidence: 99%